2017
DOI: 10.1038/s41598-017-14655-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Curative Therapeutic Vaccine (TheraVac) for the Treatment of Large Established Tumors

Abstract: Harnessing immune system to treat cancer requires simultaneous generation of tumor-specific CTLs and curtailment of tumor immunosuppressive environment. Here, we developed an immunotherapeutic regimen capable of eliminating large established mouse tumors using HMGN1, a DC-activating TLR4 agonist capable of inducing anti-tumor immunity. Intratumoral delivery of HMGN1 with low dose of Cytoxan cured mice bearing small (∅ ≈ 0.5 cm), but not large (∅ ≈ 1.0 cm) CT26 tumors. Screening for activators capable of synerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 50 publications
5
51
0
Order By: Relevance
“…In agreement with the above BPs, cellular components (CC) such as Extracellular exosome (GO:0070062, p = 4.79E‐04), Integral component of plasma membrane (GO:0005887, p = 0.0050), and Clathrin‐coated vesicle (GO:0030136, p = 0.0022) associated proteins were differentially regulated. Two KEGG pathways, Complement and coagulation cascades ( p = 5.72E‐4) and ECM‐receptor interaction ( p = 0.0343), were also enriched in the 147‐protein list, reinforcing the newly discovered role of HMGN1 in immune response …”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…In agreement with the above BPs, cellular components (CC) such as Extracellular exosome (GO:0070062, p = 4.79E‐04), Integral component of plasma membrane (GO:0005887, p = 0.0050), and Clathrin‐coated vesicle (GO:0030136, p = 0.0022) associated proteins were differentially regulated. Two KEGG pathways, Complement and coagulation cascades ( p = 5.72E‐4) and ECM‐receptor interaction ( p = 0.0343), were also enriched in the 147‐protein list, reinforcing the newly discovered role of HMGN1 in immune response …”
Section: Resultsmentioning
confidence: 68%
“…reported that extracellular HMGN1 acts as a novel alarmin that binds TLR4 and induces antigen‐specific Th1 immune responses and could be a potent immunoadjuvant by supporting T cell–mediated antitumor immunity . Recently, a curative therapeutic vaccination regimen dubbed “TheraVac” consisting of HMGN1 and resiquimod plus a checkpoint inhibitor was developed with the potential to eliminate various large tumors and induce tumor‐specific immunity . Our proteomic profiling is promising in this regard, because complement and coagulation cascades and interferon alpha or gamma responses were found to be significantly induced upon HMGN1 deletion, and therefore provides additional insights of HMGN1's role in immunity.…”
Section: Discussionmentioning
confidence: 94%
“…Immunoadjuvants, particularly endogenous ones such as HMGN1, likely present fewer nonspecific immunological side effects than exogenous adjuvants such as bacterial lipopolysaccharides. Therefore, HMGN1 has been extensively investigated in combination with other chemotherapeutic agents and activators for other TLR pathways or checkpoint inhibitors [13][14][15] , but the effective delivery of HMGN1 to tumors has confounded researchers. Here we described a simple and effective approach to load the potent N1ND immunoadjuvant on TEXs via an exosomal anchor peptide (TEX-N1ND), resulting in efficient delivery of N1ND to DCs together with TAAs.…”
Section: Discussionmentioning
confidence: 99%
“…High-mobility group nucleosome-binding protein 1 (HMGN1) improves DC maturation and activation in response to exogenous antigens and consistently induces Th1 immune responses 12 . Hence HMGN1 has been harnessed to promote generation of antitumor immune responses as DNA vaccines or in combination with chemotherapeutic agents and activators/checkpoint inhibitors in different tumor models [13][14][15] . However, only limited effects were achieved with DNA vaccines and combinatorial therapy since HMGN1 required intratumoral administration, which is not clinically applicable to most tumors.…”
mentioning
confidence: 99%
See 1 more Smart Citation